FEASIBILITY STUDY OF SOLAR CARPARK IN UTP - PAUL DANIEL, JOEL JACOB (2018)
UTP has many open carparks that are under direct sunlight during the daytime. This causes the cars to be hot and stuffy even if parked for a short time. What if, instead of just putting a normal car roof to prevent heating, we installed a solar car park. This way, we can make use of the wasted solar power in the area. The electricity produced can be directed to something beneficial like maybe to power the streetlights surrounding the area or even an electrical car charging station.This paper presents the feasibility of having a solar carpark in UTP. The main purpose of this project is to discover whether it is feasible or not to have a solar carpark in UTP. The solar carpark suggested is 20kW and is simulated using HOMER Pro MicroGrid